POSSIBILITY OF PROSPECTING IN INTERMONTANE BASINS BY TRADITIONAL GEOCHEMICAL METHODS - Kitayev N.A.; Bogatyrev P.V. (My University, 1988)
Intermontane basins with high ore potential, formed during Mesozoic-Cenozoic tectonomagmatic regeneration, constitute a broad belt in central Asia between the Siberian and the Chinese-Korean cratons, extending from the Sea of Okhotsk coast to central Mongolia. Such basins, being closed, are areas where very little or virtually no prospecting has so far been carried out and, on geologic maps, are marked as 'blank spots' on account of the extremely difficult prospecting conditions. Geochemical methods have virtually never been used for this purpose, because it was assumed that they would not yield positive results because they are covered by thick Recent alluvial and sometimes postmineral deposits, overlying any hidden ore bodies. To determine the mechanism of element migration, the authors studied the forms of gold in the fine minus 0.5-mm fraction on unconsolidated alluvial deposits above a blind, buried gold-ore show in a graben. A model is derived to describe the development of halos and dispersion trains of ore deposits in intermontane basins.
Keywords: Mesozoic; Cenozoic; Cenozoic; Mesozoic; Мезозой; Кайнозой